Influencing Factors of Employee Readiness to Adopt Advanced Manufacturing Technology (AMT) on Apparel Shop Floor in Sri Lanka - Susitha, S.D.E. (Faculty of Graduate Studies , University of Sri Jayewardenepura, 2021)
Compared with other manufacturing industries, apparel manufacturing can be classified as the most labor-intensive industry, which needs a man behind every machine. The use of advanced manufacturing technologies in the apparel shop floor is far behind compared to other industries. The researcher believes that one reason could be the lack of readiness of employees to adopt new technologies. This paper aims to provide empirical evidence on the influencing factors on employee readiness to adopt advanced manufacturing technology on the apparel shop floor, aiming for the Sri Lankan apparel industry. Following a critical review of literature, five factors, perceived usefulness, attitude, perceived ease of use, perceived management support, and techno-optimism, were tested with the data collected through a quantitative survey conducted among 118 employees using a questionnaire. The results revealed that all five factors correlate with employee readiness in various degrees. Findings suggest that apparel organisations may need to improve employee readiness before adopting advanced technologies on the shop floor to bring more success in technology adoption. The literature addressing technology adoption in apparel shop floor is scarce, and this study contributes to that gap. Further research is recommended to contribute to knowledge and find solutions to enhance technological capabilities to bring a competitive advantage to the apparel industry.
Keywords: Advanced manufacturing technology, change readiness, factors affecting employee readiness, technology readiness, apparel shop floor technology, apparel smart factory